Unexpected intrinsic catalytic function of porous boron nitride nanorods for highly efficient peroxymonosulfate activation in water treatment - Bao, Yueping (2022)
Porous boron nitride (BN) nanorods, which were synthesized via a one-stage pyrolysis, exhibited excellent catalytic performance for organics' degradation via peroxymonosulfate (PMS) activation. The origin of the unexpected catalytic function of porous BN nanorods was proposed, in which non-radical oxidation driven by the defects on porous BN dominated the sulfamethoxazole degradation via the generation of singlet oxygen (1O2). The adsorption energy between PMS and BN was calculated via density functional theory (DFT), and the PMS activation kinetics were further investigated using an electrochemical methodology. The evolution of 1O2 was verified by electron spin resonance (ESR) and chemical scavenging experiments. The observed non-radical oxidation presented a high robustness in different water matrices, combined with a series of much less toxic intermediates. The used BN was easily regenerated by heating in air, in which the B-O bond was fully recovered. These findings provide new insights for BN as a non-metal catalyst for organics' degradation via PMS activation, in both theoretical and practical prospects.